2019
DOI: 10.3389/fmicb.2019.01532
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Dynamics of Wheat Silage

Abstract: Knowledge regarding bacterial dynamics during crop ensiling is important for understanding of the fermentation process and may facilitate the production of nutritious and stable silage. The objective of this study was to analyze the bacterial dynamics associated with whole crop wheat silage with and without inoculants. Whole crop wheat was ensiled in laboratory silos, with and without Lactobacillus inoculants ( L. plantarum, L. buchneri ), for 3 months. Untreated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 67 publications
(128 reference statements)
8
57
3
Order By: Relevance
“…Microflora succession in the fermentation feed was significantly influenced by the presence of exogenous probiotics and enzymes after day 0 (Adonis test, p < 0.05). The mixed raw materials were enriched with Proteobacteria ( Pantoea , Pseudomonas ) and Ascomycota ( Alternaria , Epicoccum , Fusarium ), both of which are common endogenous bacteria and fungi, respectively, in silage and other environmental samples [ 3 , 16 , 18 , 31 , 37 ]. However, the above genera (except for Pantoea ) are undesirable and potentially pathogenic in feed [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microflora succession in the fermentation feed was significantly influenced by the presence of exogenous probiotics and enzymes after day 0 (Adonis test, p < 0.05). The mixed raw materials were enriched with Proteobacteria ( Pantoea , Pseudomonas ) and Ascomycota ( Alternaria , Epicoccum , Fusarium ), both of which are common endogenous bacteria and fungi, respectively, in silage and other environmental samples [ 3 , 16 , 18 , 31 , 37 ]. However, the above genera (except for Pantoea ) are undesirable and potentially pathogenic in feed [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Production of FF from human food production wastes has attracted significant interest because microbial fermentation can be undertaken using a wide range of substrates, preserves the nutrients, degrades antinutritional factors, and limits the growth of pathogens and mycotoxin content [ 17 ]. The addition of exogenous probiotics and, therefore, the extracellular enzymes they secrete, can enhance the production of FF by preventing decomposition, degrading macronutrients, improving overall nutritional value, improving sensory characteristics, and exerting a positive effect on the microbiome of the animal gastrointestinal tract that enhances animal health and productivity [ 3 , 17 , 18 , 19 ]. For example, the application of Lactobacillus plantarum to the fermentation of cauliflower leaf waste increased the RA of lactic acid bacteria [ 20 ], thereby resulting in more efficient lactic acid fermentation, reduced proteolysis, and reduced dry matter (DM) loss [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, representative sequence was compared using the Mothur3 software with the Silva database to gain classified information [ 20 ]. Functional genes of the bacterial communities were predicted using phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) [ 21 ]. The final predicted metagenome was analyzed by Statistical Analysis of Taxonomic and Functional Profiles (STAMP) v.2.1.3 [ 22 ] Cluster analysis produced using R software (ver.…”
Section: Methodsmentioning
confidence: 99%
“…At genus level, the dominant epiphytic bacteria associated with fresh E. nutans were Lactobacillus, Weissella, Erwinia, Pantoea, Pseudomonas, Leuconostoc, Lactococcus, and Enterobacter, which are different from the dominant epiphytic bacteria of Lactobacillus, Acetobacter, Weissella, Pseudomonas, Acinetobacter, and Burkholderia reported in fresh corn cultivated in low altitude region of Southwestern China (Guan et al, 2018), and the dominant epiphytic bacteria of Enterobacter, Pseudomonas, and Pantoea reported in soybean stalk before ensiling (Ni et al, 2017(Ni et al, , 2018, and also the dominant epiphytic bacteria of Pantoea (34.7%), Weissella (28.4%), Pseudomonas (10.4%), Exiguobacterium (7.8%), and Paenibacillus (3.4%) in fresh wheat before ensiling from the temperate oceanic climate of Germany (Keshri et al, 2019). It was suggested that altitude and climate may affect the distribution of LAB (Leong et al, 2014).…”
Section: Microbial Composition Of E Nutans Before and After Ensilingmentioning
confidence: 98%